Fertilizer Industry - Park, Murray (Woodhead Pub. ; International Fertilizer Industry Association, 2001)
This is the first comprehensive guide to the workings of an industry of crucial importance to the world's agricultural economy. Published in association with the International Fertilizer Industry Association, The fertilizer industry looks at the structure of the industry for all the key categories of fertilizer products including nitrogen, phosphate and potash fertilizers. It covers their production and end use, their implications for the environment and considers the patterns and future of the international trade.